Experimental study for improving unglazed solar system. Issue 1 (1st January 2021) - Mahmood, Afaq Jasim
Abstract: The experimental study presents an improved thermal analysis performance for the conventional unglazed transpired collector (UTC). Decreasing radiation and convection heat transfer loss to the environment and increasing heat transfer coefficient of the passing air with, first: Adding fifteen-wire mesh layers as an alternative of the perforated absorbing plate. The porous media, with a cross-sectional area of 2.2 mm× 2.2 mm and an internal diameter of 4.11 mm, located in the plenum channel of the collector to enlarge the absorbing heat area and heat transfer coefficient. Second: Fixed a 3 mm thickness of galvanized plat above the wire mesh layers for decreasing the heat loss from the unglazed solar collector to the environment. The relation of the inlet temperature, solar intensity, and the temperature difference, with a time of day, was indicated for air velocity from 2 m/s to 7 m/s. The results showed that thermal efficiency improved by increasing the airflow rate and the maximum thermal efficiency of 63.3% for seven m/s. However, the temperature difference (ΔT) was increased to a maximum value of 31.6°C, at air velocity decreased to 2 m/s. The thermal efﬁciency increased as the temperature parameter (Ti-Ta)/I reduced. When temperature parameter (Ti-Ta)/I, increased high heat loss was made. Also, there was a good agreement between the outlet temperature experimental results and the theoretical model's prediction.